A Systematic Literature Review of Education and Health in Urban Poverty - Chetri, Lamita; Baishya, Purabi (Journal of Posthumanism, 2025)
The focus of the paper is mainly on reviewing literature in the context of urban poverty by highlighting their educational as well as health aspects. The current trends of urban poverty are examined in this study as well, along with how they relate to Sustainable Development Goals. It also offers policy proposals for sustainable solutions to emerge, in order to achieve the SDGs. The review paper encompasses 60 research studies in all, and the conclusions on urban poverty and its impact on health and education has been identified from the literature. Research that has been published in all of the indexed journals has been thoroughly examined using the databases Shodhganga, J-Stor, and Google Scholar. Research conducted between 2000 and 2023 of residents of the slums has been included, with an emphasis on capturing urban poverty and its effects on both the country's overall population and its youth. Several of these research studies demonstrated the substantial impact of urban poverty on health and education. However, some other variables are also included in the study.